Violation of the Agreement Maxim Regarding the Existence of Police in the Comment Section of Bangsamahardika's Instagram Post - Maharani, Sasa (BRIN Publishing (Penerbit BRIN), 2024)
ABSTRACT This study aims to analyze the forms of impoliteness in the comment section of posts by the Instagram account Bangsamahardika, specifically focusing on violations of the agreement maxim based on Leech's politeness theory. The research adopts a descriptive qualitative approach, with data collected through digital observation of comments on five Instagram posts by Bangsamahardika during the period of December 1–10, 2024. The collected data were recorded and analyzed using pragmatic theory to understand the context and meaning of impolite comments. The findings reveal three main types of violations of the agreement maxim: identity, function, and actions of the police. First, the identity of the police, characterized by their brown uniforms, often becomes the target of criticism and satire, such as the term